TELAAH NILAI DEMOKRASI DALAM LAGU MADURA “PAJJHÂR LAGGHU” MELALUI PERSPEKTIF BUDAYA LOKAL - Syaifatul Jannah (Al-Amien Prenduan University, Sumenep, 2025)
The song Pajjhâr Lagghu is a traditional Madurese song taught in schools in Madurese language classes to introduce local culture to students. However, teaching often emphasizes only the singing aspect without exploring the democratic meaning and message contained within it. Therefore, this study aims to describe the democratic values in the song Pajjhâr Lagghu. The research method uses a qualitative approach with a literature review design. The analysis technique employs Gadamerian hermeneutics, a method of interpreting the meaning within a text. The research findings reveal that there are three democratic values in the Pajjhâr Lagghu song that teachers can adopt as efforts to foster democratic awareness. These values are time discipline, found in the lyrics of Pajjhar Lagghu arena pon nyonarah Bapak tani se tedung pon jhaga’a, the ability to control oneself so as not to disturb others, found in the lyrics ajhalan aghi sarat kawajibhan, and sensitivity (the attitude of helping others), found in the lyrics mama’mor nangharanah ban bhangsanah.